Biomaterials for the Treatment of Alzheimer’s Disease - Hadavi, Darya; Poot, André A. (Frontiers in Bioengineering and Biotechnology, 2016)
Alzheimer’s disease as a progressive and fatal neurodegenerative disease represents a huge unmet need for treatment. The low efficacy of current treatment methods is not only due to low drug potency, but also to the presence of various obstacles in the delivery routes. One of the main barriers is the blood-brain barrier. The increasing prevalence of Alzheimer’s disease and the low efficacy of current therapies have increased the amount of research on unraveling of disease pathways and development of treatment strategies. One of the interesting areas for the latter subject are biomaterials and their applications. This interest originates from the fact that biomaterials are very useful for the delivery of therapeutic agents such as drugs, proteins and/or cells, in order to treat diseases and regenerate tissues. Recently, manufacturing of nano-sized delivery systems has increased the efficacy and delivery potential of biomaterials. In this article, we review the latest developments with regard to the use of biomaterials for the treatment of Alzheimer’s disease, including nanoparticles and liposomes for delivery of therapeutic compounds as well as scaffolds for cell delivery strategies.